Structural tax reforms and public spending efficiency - Afonso, António (2022)
We empirically assess the effects of structural tax reforms on government spending efficiency in a sample of 18 OECD economies over the period 2006–2017. After calculating input spending efficiency scores, we evaluate in a panel setup the relevance for public sector efficiency of narrative tax changes. We find that: i) input efficiency scores average around 0.6–07; ii) increases in tax rates, primarily for PIT, negatively affect public sector efficiency; iii) controlling for endogeneity, increases in tax rates are still associated with lower public sector efficiency, mainly for PIT and increases in tax bases improve public sector efficiency; vi) in expansionary periods, increasing the CIT base and reducing PIT rates, positively affect public sector efficiency; ix) in contrast, during recessions efficiency improves when PIT and VAT bases increase and the CIT rate increases.